2000
DOI: 10.1056/nejm200002173420704
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Nitric Oxide Therapy for Persistent Pulmonary Hypertension of the Newborn

Abstract: Inhaled nitric oxide reduces the extent to which extracorporeal membrane oxygenation is needed in neonates with hypoxemic respiratory failure and pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
343
2
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 662 publications
(363 citation statements)
references
References 30 publications
4
343
2
14
Order By: Relevance
“…Inhaled nitric oxide decreases the need for ECMO in patients with PPHN, 3,4,6,7 and following its approval for clinical use, the number of patients entered in the national registry of ECMO patients with a diagnosis of sepsis, idiopathic PPHN or meconium aspiration declined by about 50%. 16 In a randomized trial, improvement in oxygenation occurred more frequently in infants with PPHN treated with HFOV plus iNO as compared to infants treated with either HFOV or iNO alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhaled nitric oxide decreases the need for ECMO in patients with PPHN, 3,4,6,7 and following its approval for clinical use, the number of patients entered in the national registry of ECMO patients with a diagnosis of sepsis, idiopathic PPHN or meconium aspiration declined by about 50%. 16 In a randomized trial, improvement in oxygenation occurred more frequently in infants with PPHN treated with HFOV plus iNO as compared to infants treated with either HFOV or iNO alone.…”
Section: Discussionmentioning
confidence: 99%
“…2 Most often PPHN occurs in infants with meconium aspiration syndrome (34 to 51%), pneumonia/sepsis (20 to 23%), idiopathic PPHN (17 to 25%), congenital diaphragmatic hernia (10 to 15%) or respiratory distress syndrome (9 to 12%). 3,4 Prior to the introduction, in the late 1990s, of inhaled nitric oxide (iNO), therapies for PPHN included induced alkalosis, supplemental oxygen, mechanical ventilation and neuromuscular blockade; and patients who failed to respond to these measures were treated with extracorporeal membrane oxygenation (ECMO). 5 iNO has been shown to reduce the need for ECMO in term and near-term neonates with pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No differences were seen in length of hospital stay, days on ventilator, and chronic lung disease. The Clinical Inhaled Nitric Oxide research group (CINRGI) 10 enrolled infants with PPHN (n ¼ 186) and showed similar results, with a reduction in need for ECMO from 57 to 31% (P<0.001). The primary end point in the previous three trials was a reduction in need for ECMO since, during these trials, ECMO was considered a standard treatment for PPHN not responding to conventional treatments.…”
Section: Nitric Oxide In Term Infantsmentioning
confidence: 90%
“…The need for ECMO before availability of NO was 36 to 64% when the Oxygenation Index (OI) was 24 and 44, respectively. 10,11 Four randomized, placebo controlled clinical trials have been published in near term babies with hypoxemic respiratory failure. All of them were designed to show a reduction in death and/or the need for ECMO in these infants.…”
Section: Nitric Oxide In Term Infantsmentioning
confidence: 99%